Unpacking the Reggio Emilia approach: Innovative curriculum development in early childhood education - Nurfitri, Tetin (International Journal of Nusantara Islam, 2025)
The Reggio Emilia approach is a progressive pedagogical model that positions children as active subjects in the learning process. This study is grounded in the need to gain a deeper understanding of the core principles of the Reggio Emilia approach within the context of early childhood education, particularly in relation to curriculum development and the evolving roles of teachers. The purpose of this research is to systematically examine the key concepts of the Reggio Emilia approach, including how the curriculum is constructed and how interactions between children and teachers are framed. Using a Systematic Literature Review (SLR) method, the researcher analyzed a range of relevant academic publications selected through established inclusion and exclusion criteria. The findings reveal that the Reggio-inspired curriculum is flexible, contextual, and project-based, shaped through documentation, observation, and collaboration among teachers, children, and the surrounding environment. Children are positioned as constructors of knowledge and young researchers who actively explore their world, while teachers act as facilitators, partners, and reflective researchers who support and interpret the learning process. This study concludes that the Reggio Emilia approach offers valuable contributions to the creation of participatory, meaningful, and child-centered educational practices. The findings are expected to serve as a theoretical foundation for curriculum development and pedagogical innovation in various local contexts, especially in Indonesia.